2011
DOI: 10.4149/neo_2011_03_189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CD40 expression in breast cancer and its relation to clinicopathological characteristics.

Abstract: Breast cancer is currently the most common cancer in women worldwide. For this reason, new biomarkers for better predicting response to treatment are needed. CD40, described as expressed in haematological and epithelial tumors, is linked to apoptosis and offers promise as a new predictive/ prognostic marker. We evaluated CD40 expression in formalin-fixed, paraffin-embedded samples from 181 breast carcinomas using immunohistochemical staining with CD40 antibody. Samples were divided according to hormone (oestro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Consequently, tumor-infiltrating lymphocytes have been shown to be favorable for breast cancer survival, and UPR activation is associated with tumor-infiltrating lymphocytes in breast cancer [ 63 , 64 ]. In both the METABRIC and TCGA datasets, downregulation of genes such as CD4 and CD40 may indicate decreased CD4+ T cell response or decreased CD40 -mediated apoptosis, both of which are correlated with tumor regression, better response to therapy, and higher overall breast cancer survival [ 65 , 66 ]. Furthermore, breast tumors that overexpress AGR2 exhibit downregulation of KEGG pathways epitomized by the inflammatory response, including Pathogenic Escherichia Coli infection, HTLV-1 infection, and TNF pathway (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, tumor-infiltrating lymphocytes have been shown to be favorable for breast cancer survival, and UPR activation is associated with tumor-infiltrating lymphocytes in breast cancer [ 63 , 64 ]. In both the METABRIC and TCGA datasets, downregulation of genes such as CD4 and CD40 may indicate decreased CD4+ T cell response or decreased CD40 -mediated apoptosis, both of which are correlated with tumor regression, better response to therapy, and higher overall breast cancer survival [ 65 , 66 ]. Furthermore, breast tumors that overexpress AGR2 exhibit downregulation of KEGG pathways epitomized by the inflammatory response, including Pathogenic Escherichia Coli infection, HTLV-1 infection, and TNF pathway (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD40 stimulation by its soluble recombinant human CD40 ligand directly inhibits human breast cancer cells in vitro and in SCID mice model [ 84 ]. A clinical study reported a significant difference in expression of cytoplasmic CD40 between breast cancer subtypes, and cytoplasmic expression of CD40 is related to a better prognosis [ 85 ], which suggest that CD40 may have potential as a new prognostic factor in breast cancer.…”
Section: Stimulatory Molecule Agonist Antibodiesmentioning
confidence: 99%
“…CD40 expression is associated with clinical stage, degree of metastasis and poor prognosis in melanoma [13], gastric cancer [14], and non-small cell lung cancer [15]. In contrast, CD40, frequently expressed on tumor-associated macrophages, is associated with favorable prognosis in colorectal cancer [16], head and neck squamous cell carcinoma [17] and breast cancer [18]. Furthermore, CD40 ligation strongly inhibited breast cancer growth [19] and induced ovarian cancer [20] and colon cancer cell [21] apoptosis.…”
Section: Introductionmentioning
confidence: 99%